Existence and Multiplicity of Periodic Solutions Generated by Impulses - Liu Yang; Haibo Chen (Abstract and Applied Analysis)
We investigate the existence and multiplicity of periodic solutions for a class of second-order differential systems with impulses. By using variational methods and critical point theory, we obtain such a system possesses at least one nonzero, two nonzero, or infinitely many periodic solutions generated by impulses under different conditions, respectively. Recent results in the literature are generalized and significantly improved.